2020
DOI: 10.1021/acs.inorgchem.0c02179
|View full text |Cite
|
Sign up to set email alerts
|

Chiral 3D CdSe Nanotetrapods

Abstract: Three-dimensional (3D) nanomaterials have been intensively investigated because of their unique properties and wide range of potential applications; however, the ligand-induced chirality in 3D semiconductor nanocrystals has been scarcely studied. In this paper, we report the synthesis of hydrophobic 3D CdSe nanotetrapods (Tps) with a high degree of uniformity in their morphology by using the hot-injection method. The core and arms of Tps are distinct in their crystal structure, thus creating an intracrystal he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Strain and the subsequent change of the crystal structure of nanoparticles can also cause the appearance of the optical activity in non-chiral materials 99 . By means of colloidal chemistry, nanoparticles can be synthesized in different shapes ranging from spherical dots and elongated nanorods to nanoplatelets, nanoscrolls, nanoribbons, and tetrapods; some of these shapes cause intrinsic optical activity 18 , 100 , 101 . Another way to introduce chirality is functionalization of the nanoparticle’s surface with chiral ligands, which may result in hybridization of their energy levels and/or distortion of their surface.…”
Section: Chirality: Experimental Techniques and Molecular/nanoscale E...mentioning
confidence: 99%
See 1 more Smart Citation
“…Strain and the subsequent change of the crystal structure of nanoparticles can also cause the appearance of the optical activity in non-chiral materials 99 . By means of colloidal chemistry, nanoparticles can be synthesized in different shapes ranging from spherical dots and elongated nanorods to nanoplatelets, nanoscrolls, nanoribbons, and tetrapods; some of these shapes cause intrinsic optical activity 18 , 100 , 101 . Another way to introduce chirality is functionalization of the nanoparticle’s surface with chiral ligands, which may result in hybridization of their energy levels and/or distortion of their surface.…”
Section: Chirality: Experimental Techniques and Molecular/nanoscale E...mentioning
confidence: 99%
“…Another way to introduce chirality is functionalization of the nanoparticle’s surface with chiral ligands, which may result in hybridization of their energy levels and/or distortion of their surface. Using this approach, plenty of chiral semiconductor nanoparticles have been reported, such as CdS 89 , CdSe 101 , 102 , and CdTe 103 105 quantum dots, perovskites nanocrystals 91 , and nano-sheets 106 . Moreover, it was shown that chiral quantum dots can also be synthesized without using chiral precursors or ligands, yet enantiomer nanoparticles could be separated 90 , which pointed out that their optical activity may originate from chiral defects at the particle’s surface.…”
Section: Chirality: Experimental Techniques and Molecular/nanoscale E...mentioning
confidence: 99%
“…32,33 The nanoparticle surface can be modified with an intrinsic chiral ligand generally containing functional surface-active head groups such -NH 2 , -COOH, -SH, N 3 , etc., which would allow the further attachment of any desired moiety around the NP's surface. [34][35][36][37][38][39][40] In general, the choice of functionalizing reagents depends very much on the nature of the nanoparticles; for example, thiol derivatives for gold and silver nanoparticles, carboxylic or phosphoric derivatives for metal oxides, and silane-based compounds for silica nanoparticles. This approach has been widely used in the field of biosensing and imaging and has been reviewed elsewhere.…”
Section: Reviewmentioning
confidence: 99%
“…As an ever-evolving area, the study of chiral quantum dots (QDs) is attracting substantial attention due to their huge potential in the applications of stereosensing, catalysis, , circularly polarized light emitters, and more recently spintronics and biological administrations. ,, Fundamentally, chiral QDs can be divided into several species involving (1) intrinsic chiral crystals and lattice or defects, (2) chiral ligand-induced chiral optical activity transmissions, and (3) chiral assemblies and shapes of achiral QDs. , A body of extensive reviews has well-summarized the recent progress of these nanomaterials. Moreover, to physically understand the chiral origins, exciton–exciton (including ligand–core and particle–particle) interactions, and theories of dislocations and lattice growth mechanisms, together with advanced simulation techniques such as coupled dipole method (CDM), , density functional theory (DFT), ,,, and nondegenerate coupled-oscillator (NDCO) are widely employed/combined to unveil the chiral origins and obtain CD line shapes in the past decades …”
mentioning
confidence: 99%